Plating of Ion‐Exchange Membranes: A Molecular Dynamics Study (Adv. Theory Simul. 12/2022). Issue 12 (11th December 2022) - Truszkowska, Agnieszka; Boldini, Alain; Porfiri, Maurizio
Abstract : Studying Plating of Ion‐Exchange Membranes with Molecular Dynamics In article 2200523, Agnieszka Truszkowska, Alain Boldini, and Maurizio Porfiri use molecular dynamics simulations as a benchmark to inform the selection of plating materials for ion‐exchange membranes, an appealing way to create flexible electrodes for soft sensors and actuators. Such a computational tool for optimizing the plating process is demonstrated by exploring the stability of different composites of ion‐exchange membranes. Image by Anna Sawulska, Alain Boldini, and Maurizio Porfiri.